1991
DOI: 10.1200/jco.1991.9.4.572
|View full text |Cite
|
Sign up to set email alerts
|

High-dose cytarabine for intensification of early therapy of childhood acute myeloid leukemia: a Pediatric Oncology Group study.

Abstract: In June 1984, the Pediatric Oncology Group (POG) initiated a pilot study (8498) using high-dose cytarabine (HdA; 3 g/m2) for intensification of early therapy in childhood acute myelogenous leukemia (AML) (group I). Remission induction therapy consisted of two courses of daunorubicin, cytarabine (Ara-C), and thioguanine (DAT). Postremission therapy consisted of four sequential courses, each consisting of (1) four doses of HdA (HdA4) followed by asparaginase (L-Asp), (2) etoposide (VP) plus azacytidine (Az), (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 15 publications
2
52
1
Order By: Relevance
“…5 In recent years, most pediatric oncology groups have relied increasingly on intrathecal (IT) chemotherapy for the prevention and treatment of CNS leukemia and have reduced the use of CNS irradiation. 6 In addition, new antileukemic therapies (eg, high-dose cytarabine 11 and cladribine 12 ) offer increased CNS penetration. We analyzed the clinical features and outcome of pediatric patients with and without CNS involvement in a cohort of 290 patients treated on four institutional AML protocols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In recent years, most pediatric oncology groups have relied increasingly on intrathecal (IT) chemotherapy for the prevention and treatment of CNS leukemia and have reduced the use of CNS irradiation. 6 In addition, new antileukemic therapies (eg, high-dose cytarabine 11 and cladribine 12 ) offer increased CNS penetration. We analyzed the clinical features and outcome of pediatric patients with and without CNS involvement in a cohort of 290 patients treated on four institutional AML protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Further, there is little information about the appropriate threshold (white blood cell (WBC) count in cytocentrifuged CSF) needed to diagnose CNS involvement in AML. The threshold used by an Italian research group, 4 The Pediatric Oncology Group (POG), 6 and St Jude 7 is the presence of any blast cells (regardless of cell count). The Children's Cancer Group (CCG) 8 and the Berlin-Frankfurt-Münster (BFM) group 3 use a threshold of 5 and 10 WBC/ml, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown an unfavorable outcome in very young patients, 18,22 others have found comparable survival rates between the two age groups, 17,21,[23][24][25][26] while still others indicated a better prognosis for infants. 19 are very few data on the blast cell genetics of infants with AML. Only four studies have attempted to assess the prognostic significance of MLL/11q23 rearrangements, the most common genetic lesion in infants with AML.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies combined infants less than 12 months of age with those 1-2 years old in a single group. [17][18][19][20][21][22] Second, the prognosis of AML in very young patients as compared to older patients varied among different clinical protocols, underscoring the overriding importance of treatment efficacy. Some studies have shown an unfavorable outcome in very young patients, 18,22 others have found comparable survival rates between the two age groups, 17,21,[23][24][25][26] while still others indicated a better prognosis for infants.…”
Section: Introductionmentioning
confidence: 99%
“…Other changes were introduced in the treatment regimen: the consolidation course of EORTC 58872, comprising four fortnightly doses of MTZ and which had induced very severe and prolonged neutropenia, was deleted and a combination of highdose Ara-C and the anthracycline to which the patient had been randomized was substituted for it. 11,12 The second intensification was the 'DCTER' course according to the CCG 2861 protocol. 4,5 The third intensification remained identical to the second intensification of 58872.…”
Section: Introductionmentioning
confidence: 99%